NALISIS TOKOH DAN PENOKOHAN SERTA NILAI-NILAI PENDIDIKAN RELIGIUS PADA NOVEL SURAT KECIL UNTUK TUHAN KARYA AGNES DAVONAR - Febriasari, Diani (Widya Warta, 2017)
ABSTRACT In this global era, Indonesia society are facing a crisis of values and character. It's seen from increasing cases of rape, fights, rustling, drugs, alcohols, conflict of inter-religious, ethnics, racial, etc. The complexity of this problem must be balanced with incessant instill of religious values. Based on the background of the problems above, the purpose of this study was to know the figures and characterization analysis and also presentation forms of religious education values in novel "Surat Kecil Untuk Tuhan" works by Agnes Davonar.Â This study used a qualitative approach. According to the research, found that the character of figures in the novel "Surat Kecil Untuk Tuhan", delivered by the author dramatically through figures conversation, figures thought and figures act or behavior. The main character was Keke who has vibrant, smart, steadfast and unyielding character. The additional figure was Jodi who responsibility, wise, patient and unyielding too. The next was fully attentive Andi, Kiki who attentive and smart, There were faithfull and obedient Mr. Iyus, Bibi was fully attentive, wise Prof. Lukman and friendly Prof. Muklis. Not left behind, Keke's friends such Fadha who's confident and 'tomboy', active Shifa, shy girl Maya and Idha, genius Andini also Adhinda who's noisy and spoiled. Form of religious values presented by author through the figures in the novel "Surat Kecil Untuk Tuhan". Religious values seen is diligent worship, obedient, surrender and gratefull.